Alloy suitable for air-cooled diesel engine cylinder cover and preparation method thereof
The aluminum alloy with a unique composition and microstructure addresses the high-temperature performance and thermal conductivity issues of wind-cooled diesel engine cylinder covers, offering superior mechanical and thermal stability through a specific processing method.
Patent Information
- Application Number
- CN202411891353.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-18
AI Technical Summary
Wind-cooled diesel engine cylinder covers face challenges with poor high-temperature performance and low thermal conductivity, particularly in severe service environments between 250-300°C, and the high cost of using Scandium to enhance these properties.
A specific aluminum alloy composition including Cu, Ni, Mn, Zr, Ti, Co, Sb, Fe, Si, Mg, Ag, Er, and Be, with a microstructure of θ', τ, δ, and γ phases, is developed, which is processed through a method involving preheating, melting, and heat treatment to achieve enhanced mechanical properties and thermal conductivity.
The alloy exhibits improved mechanical strength and thermal stability at room and elevated temperatures, with high thermal conductivity and resistance to aging, effectively addressing the limitations of traditional Al-Cu alloys.
Smart Images

Figure CN119640110A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nonferrous metals, and in particular relates to an alloy suitable for an air-cooled diesel engine cylinder head and a preparation method thereof. Background Art
[0002] RR350 aluminum alloy has good high temperature strength and long-lasting strength, and excellent comprehensive performance. RR350 alloy belongs to the A1-Cu-Ni system, which is composed of A1-5Cu-1.5Ni with a variety of other elements added. The precipitation transformation products during aging heat treatment are very complex. According to different conditions, the possible transformation products include GP zone θ”, θ', θ, and T Mn '、T Ni '、T Mn , T Ni wait.
[0003] The usual approach to studying the heat resistance of Al-Cu-Ni based age-hardenable alloys is to enhance their heat resistance by changing the Cu / Ni ratio and adjusting the content of Al3Ni, Al3CuNi or Al7Cu4Ni phases in the alloy. Another solution is to introduce independent Al3X (X = Sc, Zr, Er, etc.) precipitation outside the original precipitation sequence by adding rare earth / transition elements such as Sc, Zr, and Er. The Al3X precipitation phase generally has excellent thermal stability and is recognized as an effective means to improve the high-temperature service performance of aluminum-based alloys. However, research on heat-resistant alloys under the combined action of Ag, Er, and Be is basically blank. Although Sc is the most effective modifier in aluminum alloys, adding Sc to aluminum alloys can significantly improve the comprehensive properties of the alloy. However, due to the high price of Sc, its wide application in alloys is limited. Summary of the invention
[0004] The purpose of the present invention is to provide an alloy suitable for an air-cooled diesel engine cylinder head and a preparation method thereof, so as to solve the problems of poor heat resistance and low thermal conductivity of the air-cooled diesel engine cylinder head in a harsh service environment of 250-300°C, and high cost of changing performance by adding Sc.
[0005] The present invention adopts the following technical solution: an alloy suitable for an air-cooled diesel engine cylinder head, comprising, by weight percentage:
[0006] Cu: 4.5~5.5%, Ni: 1.3~1.8%, Mn: 0.2~0.3%, Zr: 0.1~0.3%, Ti: 0.15~0.26%, Co: 0.11~0.35%, Sb: 0.15~0.29%, Fe≤0.50%, Si≤0.30%, Mg≤0.05%, Ag: 0.2~0.31%, Er: 0.05~0.11%, Be: 0.05~0.09%, and the rest is Al.
[0007] Furthermore, the alloy has a tensile strength of 350 to 359.40 MPa, a yield strength of 283.49 to 286.84 MPa, a thermal conductivity of >142.13 W / (m·k), and an elongation of 3.18 to 4.32% at room temperature;
[0008] The alloy has a tensile strength of 214.59-227.95 MPa at 250°C, a yield strength of 176.47-188.26 MPa, a thermal conductivity of >164.83 W / (m·k), and an elongation of 6.98-9.61%;
[0009] The alloy has a tensile strength of 161.45-167.13 MPa at 300° C., a yield strength of 130.59-135.27 MPa, a thermal conductivity of more than 164.71 W / (m·k), and an elongation of 8.75-15.76%.
[0010] Furthermore, four strengthening phases, namely θ', τ, δ and γ, exist in the alloy.
[0011] A method for preparing an alloy suitable for an air-cooled diesel engine cylinder head, comprising:
[0012] Step 1: Heat-treat the blocky Zr, Ni, and RE at 220°C for 2 to 4 hours;
[0013] Step 2: Mix the preheated bulk Zr, Ni, RE and other bulk raw materials together and place them in a crucible;
[0014] Step 3: Smelt the crucible containing the raw materials. After all the raw materials are melted and the alloy solution is at 715±20°C, press the refining agent into the alloy solution, rotate it slowly and evenly until the reaction stops, then take out the bell jar to obtain the refined aluminum liquid, and let it stand to obtain an aluminum alloy ingot;
[0015] Step 4: The aluminum alloy ingot is kept at 530-535°C for 8 hours at a heating rate of 15-20°C / hour, then heated to 540-545°C with the furnace, kept for 7 hours, and then quenched in 70-75°C water to obtain an alloy sample;
[0016] Step 5: Perform aging treatment on the alloy sample at 160°C for 20 to 24 hours, then take it out and air cool it.
[0017] Furthermore, the aluminum alloy ingot includes, by weight percentage, Cu: 4.5-5.5%, Ni: 1.3-1.8%, Mn: 0.2-0.3%, Zr: 0.1-0.3%, Ti: 0.15-0.26%, Co: 0.11-0.35%, Sb: 0.15-0.29%, Fe≤0.50%, Si≤0.30%, Mg≤0.05%, Ag: 0.2-0.31%, Er: 0.05-0.11%, Be: 0.05-0.09%, and the rest is Al.
[0018] Furthermore, the preheating temperature and time in step 2 are 180-220° C. for 10-15 min.
[0019] The beneficial effects of the present invention are:
[0020] The present invention improves the microstructure and strength by combining cluster-precipitation behavior, so that the tensile strength of the alloy at room temperature is greater than 350MPa, and the tensile strength at 250°C and 300°C reaches 210MPa and 160MPa respectively;
[0021] The present invention introduces Ag, Er, and Be elements to modify the matrix alloy, refine the grains, and the introduced elements not only produce a solid solution strengthening effect with the matrix alloy, but also form intermetallic compounds to hinder dislocation movement, thereby improving the strength of the alloy. The Ag element inhibits the diffusion of Cu atoms, making the θ' phase in the alloy finer and improving the toughness of the alloy, thereby achieving excellent mechanical properties at room temperature and in a high-temperature service environment of 250 to 300°C. Compared with traditional Al Cu alloys, the alloy has higher mechanical properties at room temperature and better anti-aging ability at high temperatures.
[0022] The main strengthening phase of the Al-Cu-Ni alloy prepared by the present invention is not the θ' phase in the traditional Al-Cu alloy, but the coexistence of four strengthening phases of θ', τ, δ, and γ. Compared with the θ' phase with a thermal stability of 150-200°C in the traditional Al-Cu alloy, the strengthening phases of τ, δ, and γ with a thermal stability of 250-350°C are introduced; thereby achieving excellent mechanical properties at room temperature and in a high-temperature service environment of 250-300°C; and the addition of Ag will inhibit the precipitation of the strengthening phase in the alloy, thereby retaining more copper atoms in the alloy matrix; this will enhance solid solution strengthening, help improve the strength and toughness of the aluminum-copper alloy, and then improve the fatigue performance of the alloy;
[0023] The present invention has very high high temperature performance and excellent high temperature stability. This is because the alloy contains many transition elements. Under the condition of multi-component composite strengthening, the solid solution precipitation can be inhibited, so that the alloy can still maintain the fine structure of the metastable phase after long-term heat preservation, which has a significant effect on improving the thermal stability of the alloy. Therefore, the alloy not only has good high temperature and room temperature performance, but also has very little hardness loss after long-term heat preservation.
[0024] The present invention adopts Er to replace the Sc element to prepare the Al-Cu-Ni alloy with Ag, Er and Be composite modification, thereby improving the heat resistance of the alloy in a harsh service environment of 250-300°C.
[0025] The addition of Er in the present invention will cause the alloy to generate Al3Er particles as heterogeneous nucleation points of grains during solidification, thereby promoting α-Al nucleation. At the same time, this phase has high hardness and brittleness, is easily refined during thermal deformation, and is dispersed in the matrix to form a strong stress field, which hinders the movement of dislocations and can play a role in heterogeneous strengthening. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The room temperature tensile engineering stress-engineering strain curves of Examples 1-5 and Comparative Examples 6-7;
[0027] Figure 2 The engineering stress-engineering strain curves of Examples 1-5 and Comparative Examples 6-7 stretched at 250°C;
[0028] Figure 3 The engineering stress-engineering strain curves of Examples 1-5 and Comparative Examples 6-7 stretched at 300°C;
[0029] Figure 4 The thermal conductivity bar graphs of Examples 1, 3 and Comparative Example 7 at room temperature, 250°C and 300°C;
[0030] Figure 5 The following are the SEM photos and spectra of the alloy of Example 3. DETAILED DESCRIPTION
[0031] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0032] The invention discloses an alloy suitable for an air-cooled diesel engine cylinder head. The alloy comprises, by weight percentage, 4.5-5.5% Cu, 1.3-1.8% Ni, 0.2-0.3% Mn, 0.1-0.3% Zr, 0.15-0.26% Ti, 0.11-0.35% Co, 0.15-0.29% Sb, Fe≤0.50%, Si≤0.30%, Mg≤0.05%, Ag: 0.2-0.31%, Er: 0.05-0.11%, Be: 0.05-0.09% and the remainder is Al.
[0033] The tensile strength of the alloy at room temperature is 350-359.40Mpa, the yield strength is 283.49-286.84Mpa, the thermal conductivity is greater than 142.13W / (m·k), and the elongation is 3.18-4.32%; the tensile strength of the alloy at 250°C is 214.59-227.95Mpa, the yield strength is 176.47-188.26MPa, the thermal conductivity is greater than 164.83W / (m·k), and the elongation is 6.98-9.61%; the tensile strength of the alloy at 300°C is 161.45-167.13Mpa, the yield strength is 130.59-135.27MPa, the thermal conductivity is greater than 164.71W / (m·k), and the elongation is 8.75-15.76%. The alloy contains four strengthening phases of θ', τ, δ, and γ.
[0034] The present invention also discloses a method for preparing an alloy suitable for an air-cooled diesel engine cylinder head, comprising:
[0035] Step 1: Heat-treat the blocky Zr, Ni, and RE at 220°C for 2 to 4 hours;
[0036] Step 2: Mix the preheated bulk Zr, Ni, RE and other bulk raw materials together and place them in a crucible;
[0037] Step 3: Smelt the crucible containing the raw materials. After all the raw materials are melted and the alloy solution is at 715±20°C, press the refining agent into the alloy solution, rotate it slowly and evenly until the reaction stops, then take out the bell jar to obtain the refined aluminum liquid, and let it stand to obtain an aluminum alloy ingot;
[0038] Step 4: The aluminum alloy ingot is kept at 530-535°C for 8 hours at a heating rate of 15-20°C / hour, then heated to 540-545°C with the furnace, kept for 7 hours, and then quenched in 70-75°C water to obtain an alloy sample;
[0039] Step 5: Perform aging treatment on the alloy sample at 160°C for 20 to 24 hours, then take it out and air cool it.
[0040] The aluminum alloy ingot includes, by weight percentage, Cu: 4.5-5.5%, Ni: 1.3-1.8%, Mn: 0.2-0.3%, Zr: 0.1-0.3%, Ti: 0.15-0.26%, Co: 0.11-0.35%, Sb: 0.15-0.29%, Fe≤0.50%, Si≤0.30%, Mg≤0.05%, Ag: 0.2-0.31%, Er: 0.05-0.11%, Be: 0.05-0.09%, and the rest is Al.
[0041] The preheating temperature and time in step 2 are 180-220° C. for 10-15 minutes.
[0042] Example 1
[0043] The alloy of this embodiment includes, by weight percentage, Cu: 5.37%, Ni: 1.53%, Mn: 0.24%, Zr: 0.18%, Ti: 0.21%, Co: 0.30%, Sb: 0.29%, Fe: 0.46%, Si: 0.27%, Mg: 0.03%, Ag: 0.31%, Er: 0.11%, Be: 0.09%, and the rest is Al.
[0044] The preparation method of the alloy of this embodiment includes:
[0045] Step 1: Heat-treat the block Zr, Ni, and RE at 220±10℃ for 4h;
[0046] Step 2: Preheat the bulk Zr, Ni, and RE at 180°C for 10 minutes, mix them with the remaining bulk raw materials, and place them in a crucible;
[0047] Step 3: Melt the crucible containing the raw materials. After all the raw materials are melted and the alloy solution is at 715±20°C, use a bell jar to press the refining agent into the alloy solution in two batches, 10 cm away from the bottom of the crucible, and rotate slowly and evenly until the reaction stops, then take out the bell jar to obtain an aluminum alloy ingot;
[0048] Step 4: The aluminum alloy ingot was kept at 535°C for 8 hours at a heating rate of 20°C / hour, then heated to 545°C with the furnace, kept for 7 hours, and then quenched in 75°C water to obtain an alloy sample;
[0049] Step 5: Perform aging treatment on the alloy sample at 160℃ for 24 hours, then take it out and air cool it.
[0050] The alloy obtained in Example 1 was tested. The properties of the alloy obtained in Example 1 are shown in Table 1, Table 2, and Table 3.
[0051] Example 2
[0052] The alloy of this embodiment includes, by weight percentage, Cu: 4.95%, Ni: 1.55%, Mn: 0.20%, Zr: 0.3%, Ti: 0.26%, Co: 0.11%, Sb: 0.15%, Fe: 0.45%, Si: 0.26%, Mg: 0.05%, Ag: 0.2%, Er: 0.05%, Be: 0.05%, and the rest is Al.
[0053] The preparation method of the alloy of this embodiment is the same as that of embodiment 1, except that:
[0054] In step 1, the heat treatment is performed for 2 hours;
[0055] Preheat at 200°C for 10 minutes in step 2;
[0056] In step 4, the temperature is kept at 530°C for 8 hours with a heating rate of 15°C / hour, then the temperature is raised to 540°C with the furnace, and after keeping the temperature for 7 hours, the alloy sample is quenched in 70°C water and then air-cooled to obtain the alloy sample.
[0057] In step 5, the alloy sample is aged at 160° C. for 20 hours, and then air-cooled after being taken out.
[0058] The alloy obtained in Example 2 was tested, and the properties of the alloy obtained in Example 2 are shown in Tables 1 and 2.
[0059] Example 3
[0060] The alloy of this embodiment includes, by weight percentage, Cu: 5.09%, Ni: 1.8%, Mn: 0.30%, Zr: 0.1%, Ti: 0.22%, Co: 0.20%, Sb: 0.25%, Fe: 0.43%, Si: 0.28%, Mg: 0.04%, Ag: 0.2%, Er: 0.11%, Be: 0.08%, and the rest is Al.
[0061] The preparation method of the alloy of this embodiment is the same as that of embodiment 1, except that:
[0062] In step 1, the heat treatment is carried out for 3 hours;
[0063] Preheat at 220°C for 10 minutes in step 2;
[0064] In step 4, the temperature is kept at 530°C for 8 hours with a heating rate of 15°C / hour, then the temperature is raised to 540°C with the furnace, and after keeping the temperature for 7 hours, the alloy sample is quenched in 70°C water and then air-cooled to obtain the alloy sample.
[0065] In step 5, the alloy sample is aged at 160° C. for 22 hours, and then air-cooled after being taken out.
[0066] The alloy obtained in Example 3 was tested, and the properties of the alloy obtained in Example 3 are specifically shown in Table 1, Table 2, and Table 3.
[0067] like Figure 5 As shown in the figure, (a) (b) (c) are SEM photos of the alloy prepared in this embodiment at different magnifications, and (d) (e) (f) are EDS point scanning spectra of the phase shown in Figure (c). It can be seen from the figure that the alloy phase prepared in this embodiment is mainly composed of a black base phase, a closed or semi-closed network structure and a small amount of gray block phase. Combined with the spectrum, it can be seen that the white network phase is δ-Al3CuNi, the gray network phase is γ-Al7Cu4Ni, the gray strip phase is θ-Al2Cu phase, and a small amount of gray block phase is T-Al 20 Cu2Mn3, black matrix phase is α-Al.
[0068] Example 4
[0069] The alloy of this embodiment includes, by weight percentage, Cu: 4.5%, Ni: 1.3%, Mn: 0.25%, Zr: 0.25%, Ti: 0.15%, Co: 0.25%, Sb: 0.12%, Fe: 0.45%, Si: 0.26%, Mg: 0.05%, Ag: 0.25%, Er: 0.75%, Be: 0.05%, and the rest is Al.
[0070] The preparation method of the alloy of this embodiment is the same as that of embodiment 1, except that:
[0071] In step 1, the heat preservation treatment is performed for 3.5 hours;
[0072] Preheat at 200°C for 15 minutes in step 2;
[0073] In step 4, the temperature is kept at 530°C for 8 hours with a heating rate of 15°C / hour, then the temperature is raised to 540°C with the furnace, and after keeping the temperature for 7 hours, the alloy sample is quenched in 70°C water and then air-cooled to obtain the alloy sample.
[0074] In step 5, the alloy sample is aged at 160° C. for 21 hours, and then air-cooled after being taken out.
[0075] The alloy obtained in Example 4 was tested. The properties of the alloy obtained in Example 4 are shown in Tables 1 and 2.
[0076] Example 5
[0077] The alloy of this embodiment includes, by weight percentage, Cu: 5.5%, Ni: 1.5%, Mn: 0.25%, Zr: 0.25%, Ti: 0.25%, Co: 0.35%, Sb: 0.25%, Fe: 0.45%, Si: 0.26%, Mg: 0.05%, Ag: 0.2%, Er: 0.05%, Be: 0.05%, and the rest is Al.
[0078] The preparation method of the alloy of this embodiment is the same as that of embodiment 1, except that:
[0079] In step 1, the heat treatment is performed for 4 hours;
[0080] Preheat at 200°C for 10 minutes in step 2;
[0081] In step 4, the temperature is kept at 530°C for 8 hours with a heating rate of 15°C / hour, then the temperature is raised to 540°C with the furnace, and after keeping the temperature for 7 hours, the alloy sample is quenched in 70°C water and then air-cooled to obtain the alloy sample.
[0082] In step 5, the alloy sample is aged at 160° C. for 20 hours, and then air-cooled after being taken out.
[0083] The alloy obtained in Example 5 was tested. The properties of the alloy obtained in Example 5 are shown in Tables 1 and 2.
[0084] Comparative Example 6
[0085] The alloy of this comparative example includes, by weight percentage, Cu: 5.3%, Ni: 1.5%, Mn: 0.23%, Zr: 0.18%, Ti: 0.22%, Co: 0.31%, Sb: 0.25%, Fe: 0.46%, Si: 0.27%, Mg: 0.05%, and the rest is Al.
[0086] The preparation method of the alloy of this comparative example comprises:
[0087] The preparation method of the alloy in this comparative example is the same as that in Example 1, except that:
[0088] In step 4, the alloy sample is kept at 530°C for 8 hours, then heated to 540°C with the furnace, kept at 70°C for 7 hours, and then quenched in 70°C water, and then air-cooled to obtain the alloy sample;
[0089] In step 5, the alloy sample is aged at 210° C. for 14 hours and then air-cooled.
[0090] The alloy obtained in Comparative Example 6 was tested, and the properties of the alloy obtained in Comparative Example 6 are specifically shown in Tables 1 and 2.
[0091] Comparative Example 7
[0092] The alloy of this comparative example includes, by weight percentage, Cu: 4.9%, Ni: 1.63%, Mn: 0.25%, Zr: 0.2%, Ti: 0.19%, Co: 0.31%, Sb: 0.25%, Fe: 0.43%, Si: 0.26%, Mg: 0.03%, and the remainder is Al.
[0093] The preparation method of the alloy of this comparative example comprises:
[0094] The preparation method of the alloy in this comparative example is the same as that in Example 1, except that:
[0095] In step 4, the alloy sample is kept at 530°C for 8 hours, then heated to 540°C with the furnace, kept at 70°C for 7 hours, and then quenched in 70°C water, and then air-cooled to obtain the alloy sample;
[0096] In step 5, the alloy sample is aged at 210° C. for 14 hours and then air-cooled.
[0097] The alloy obtained in Comparative Example 7 was tested, and the properties of the alloy obtained in Comparative Example 7 are specifically shown in Table 1, Table 2, and Table 3.
[0098] Table 1 Comparison of room temperature performance of Examples 1-5 and Comparative Examples 6-7
[0099] Alloy code Tensile strength / MPa Yield strength / MPa Elongation / % Example 1 353.18 285.72 3.71 Example 2 353.03 286.84 3.57 Example 3 355.45 286.59 3.84 Example 4 350.31 283.49 3.18 Example 5 359.40 284.92 4.32 Comparative Example 6 (RR350) 288 238 2 Comparative Example 7 (RR350) 275 215 1.65
[0100] Table 2 Comparison of high temperature performance of Examples 1-5 and Comparative Examples 6-7
[0101]
[0102]
[0103] Table 3 Comparison of thermal conductivity of Examples 1, 3 and Comparative Example 7 (thermal conductivity unit: W / (m·k))
[0104]
[0105] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. An alloy suitable for an air-cooled diesel engine cylinder head, characterized in that: In terms of weight percentage, it includes: Cu: 4.5~5.5%, Ni: 1.3~1.8%, Mn: 0.2~0.3%, Zr: 0.1~0.3%, Ti: 0.15~0.26%, Co: 0.11~0.35%, Sb: 0.15~0.29%, Fe≤0.50%, Si≤0.30%, Mg≤0.05%, Ag: 0.2~0.31%, Er: 0.05~0.11%, Be: 0.05~0.09%, and the rest is Al.
2. The alloy suitable for air-cooled diesel engine cylinder head according to claim 1, characterized in that: The alloy has a tensile strength of 350 to 359.40 MPa, a yield strength of 283.49 to 286.84 MPa, a thermal conductivity of >142.13 W / (m·k), and an elongation of 3.18 to 4.32% at room temperature; The alloy has a tensile strength of 214.59-227.95 MPa at 250°C, a yield strength of 176.47-188.26 MPa, a thermal conductivity of >164.83 W / (m·k), and an elongation of 6.98-9.61%; The alloy has a tensile strength of 161.45-167.13 MPa at 300° C., a yield strength of 130.59-135.27 MPa, a thermal conductivity of more than 164.71 W / (m·k), and an elongation of 8.75-15.76%.
3. The alloy suitable for air-cooled diesel engine cylinder head according to claim 1, characterized in that: There are four strengthening phases of θ', τ, δ and γ in the alloy.
4. A method for preparing an alloy suitable for an air-cooled diesel engine cylinder head, characterized in that: include: Step 1: Heat-treat the blocky Zr, Ni, and RE at 220°C for 2 to 4 hours; Step 2: Mix the preheated bulk Zr, Ni, RE and other bulk raw materials together and place them in a crucible; Step 3: Smelt the crucible containing the raw materials. After all the raw materials are melted and the alloy solution is at 715±20°C, press the refining agent into the alloy solution, rotate it slowly and evenly until the reaction stops, then take out the bell jar to obtain the refined aluminum liquid, and let it stand to obtain an aluminum alloy ingot; Step 4: The aluminum alloy ingot is kept at 530-535°C for 8 hours at a heating rate of 15-20°C / hour, then heated to 540-545°C with the furnace, kept for 7 hours, and then quenched in 70-75°C water to obtain an alloy sample; Step 5: Perform aging treatment on the alloy sample at 160°C for 20 to 24 hours, then take it out and air cool it.
5. The method for preparing an alloy suitable for an air-cooled diesel engine cylinder head according to claim 4, characterized in that: The aluminum alloy ingot includes, by weight percentage, Cu: 4.5-5.5%, Ni: 1.3-1.8%, Mn: 0.2-0.3%, Zr: 0.1-0.3%, Ti: 0.15-0.26%, Co: 0.11-0.35%, Sb: 0.15-0.29%, Fe≤0.50%, Si≤0.30%, Mg≤0.05%, Ag: 0.2-0.31%, Er: 0.05-0.11%, Be: 0.05-0.09%, and the rest is Al.
6. The method for preparing an alloy suitable for an air-cooled diesel engine cylinder head according to claim 4, characterized in that: The preheating temperature and time in step 2 are 180-220° C. for 10-15 minutes.